TYPE 2 DIABETES MELLITUS AS A DETERMINANT OF CARDIOVASCULAR COMPLICATIONS DEVELOPMENT - Nazarova S. K.; Mirzarakhimova N. I. (Modern American Journals, 2026)
Type 2 diabetes mellitus represents a major global public health challenge and is strongly associated with an increased risk of cardiovascular morbidity and mortality. The present study aims to analyze type 2 diabetes mellitus as a key pathogenic factor contributing to the development of cardiovascular complications. The research is based on the analysis of clinical, metabolic, and epidemiological data reflecting the impact of chronic hyperglycemia, insulin resistance, dyslipidemia, and systemic inflammation on the cardiovascular system. Particular attention is given to the mechanisms linking diabetes with atherosclerosis progression, endothelial dysfunction, arterial stiffness, and myocardial structural remodeling. The results indicate that type 2 diabetes mellitus significantly accelerates the development of ischemic heart disease, hypertension, heart failure, and cerebrovascular disorders, even in the absence of overt clinical symptoms at early stages. The findings emphasize that cardiovascular complications often develop subclinically and progress more aggressively in patients with type 2 diabetes. These observations highlight the necessity of early identification of cardiovascular risk factors, comprehensive metabolic control, and integrated preventive strategies aimed at reducing cardiovascular burden in patients with type 2 diabetes mellitus.
Keywords: Type 2 diabetes mellitus; cardiovascular complications; atherosclerosis; endothelial dysfunction; insulin resistance; cardiovascular risk.